Employment, exchange rates and labour market rigidity - Alexandre, Fernando (2010)
There is increasing evidence that the interaction between shocks and labour market institutions is crucial to understanding the dynamics of employment. In this paper, we show that the inclusion of labour adjustment costs in a trade model affects the impact of exchange rate movements on employment. We also explore how labour market rigidities interact with the degree of exposure to international competition and with the technology level. Our model-based predictions are consistent with estimates obtained using panel data for 23 OECD countries. Namely, our estimates suggest that employment in low-technology sectors that have a very high degree of openness to trade and are located in countries with more flexible labour markets are more sensitive to exchange rate changes. Our model and estimates therefore provide additional evidence on the importance of interacting external shocks and labour market institutions.